RISK FACTORS INFLUENCING ENTEROCOLITIS DEVELOPMENT IN PEDIATRIC PATIENTS WITH HIRSCHSPRUNG’S DISEASE - Andro Pramana Witarto; Alpha Fardah Athiyyah; I.G.B. Adria Hariastawa; I Gusti Made Reza Gunadi Ranuh (Jurnal Berkala Epidemiologi, 2020)
Background: Hirschsprung-associated enterocolitis (HAEC) is one of the worst and most common complications of Hirschsprung’s disease (HD). The mortality rate of HD patients with enterocolitis is still considered to be higher compared to that of those without enterocolitis. Purpose: This study aimed to identify and evaluate potential risk factors for HAEC development. Methods: A cross-sectional study was conducted using secondary data from the medical records of HD patients treated from January 2015 to September 2018 at Regional Public Hospital (RSUD) Dr. Soetomo, Surabaya. The inclusion criteria were HD patients who had or had not experienced enterocolitis. The analysis was done by comparing the presence of risk factors between groups of HD patients with and without preoperative and/or postoperative HAEC. The results were presented as the median value and frequency. To evaluate further, a prevalence ratio (PR) with a 95% confidence interval was performed. The Mann–Whitney U test was also performed with a significance level of p < 0.05 for one factor: length of aganglionic intestinal segments. Results: This study showed that 12 of the 40 HD patients studied (30%) had experienced enterocolitis. The risk of developing HAEC was associated with patients who had a history of previous enterocolitis (PR 6.60 [2.94 < PR < 14.80]). Regarding surgical details, patients who had had surgery only once (31.30% compared to 14.30%), surgery with one surgical method (29.40% compared to 20.00%), and a primary procedure had a higher incidence of HAEC (29.40% compared to 27.30%). Conclusion: HD patients with a history of previous enterocolitis were found to have a higher risk of developing HAEC.